C‐terminal of human histamine H1 receptors regulates their agonist‐induced clathrin‐mediated internalization and G‐protein signaling. Issue 4 (15th September 2016) - Hishinuma, Shigeru; Nozawa, Hiroki; Akatsu, Chizuru; Shoji, Masaru
Abstract: It has been suggested that the agonist‐induced internalization of G‐protein‐coupled receptors from the cell surface into intracellular compartments regulates cellular responsiveness. We previously reported that Gq/11 ‐protein‐coupled human histamine H1 receptors internalized via clathrin‐dependent mechanisms upon stimulation with histamine. However, the molecular determinants of H1 receptors responsible for agonist‐induced internalization remain unclear. In this study, we evaluated the roles of the intracellular C‐terminal of human histamine H1 receptors tagged with hemagglutinin (HA) at the N‐terminal in histamine‐induced internalization in Chinese hamster ovary cells. The histamine‐induced internalization was evaluated by the receptor binding assay with [ 3 H]mepyramine and confocal immunofluorescence microscopy with an anti‐HA antibody. We found that histamine‐induced internalization was inhibited under hypertonic conditions or by pitstop, a clathrin terminal domain inhibitor, but not by filipin or nystatin, disruptors of the caveolar structure and function. The histamine‐induced internalization was also inhibited by truncation of a single amino acid, Ser487, located at the end of the intracellular C‐terminal of H1 receptors, but not by its mutation to alanine. In contrast, the receptor‐G‐protein coupling, which was evaluated by histamine‐induced accumulation of [ 3 H]inositol phosphates, was potentiated by truncation of Ser487, but was lost by its mutation to alanine. These results suggest that the intracellular C‐terminal of human H1 receptors, which only comprises 17 amino acids (Cys471‐Ser487), plays crucial roles in both clathrin‐dependent internalization of H1 receptors and G‐protein signaling, in which truncation of Ser487 and its mutation to alanine are revealed to result in biased signaling toward activation of G‐proteins and clathrin‐mediated internalization, respectively. Abstract : The short C‐terminal tail (Cys471‐Ser487; 17 amino acids) of human histamine H1 receptors tagged with hemagglutinin (HA) at the N‐terminal was revealed to play crucial roles in regulation of both histamine‐induced internalization of H1 receptors and G‐protein signaling, in which truncation of Ser487 and mutation of either Thr478 or Ser487 to alanine resulted in biased signaling toward activation of G‐proteins and clathrin‐mediated internalization, respectively.